Redeeming love [videorecording (DVD)] - Cowen, Abigail, 1998-; Lewis, Tom (Thomas Elliot); Marshall-Green, Logan, 1976-; Rivers, Francine, 1947- (Universal, 2022)
Sold into prostitution as a child, Angel knows nothing but betrayal. Can her heart ever be mended?